Modernity of Women Subject in Eka Kurniawan’ Cantik Itu Luka (2002): A Study of Post-Colonial Feminist Literary Criticism - Maisyaroh Febriana Putri; Dwi Susanto (MOZAIK HUMANIORA, 2024)
This study aims to dismantle the narrative of the female subject’s modernity which was built by the author as a representative of a social group or class. In order to achieve this objective, the researchers used qualitative approach, which prioritizes data quality to data size. The data in this study is the novel Cantik Itu Luka by Eka Kurniawan, and other information related to the research topic. Then, the data were analyzed using binary opposition deconstruction and postcolonial feminism theory. Data analysis focuses on the narrative structure of the text and its ideas regarding colonial discourse and the narrative construction of the modernity of female subjects, as well as the author's historical and sociological context in relation to the text. The results show that the construction of the female subject presented in the text Cantik Itu Luka (2002) is a woman who is resistant to the discourse of modernity. In the context of colonial discourse, the female subject is a woman who participates in the rebellion against patriarchal cultural oppression and globalization. The discourse of modernity built by Eka Kurniawan is that women are required to maintain their national identity amidst the commotion of global culture. The construction of the female subject in the text is an ideal formed by male critical intellectual groups to represent and advocate women who have difficulty getting space and position in the social order.